FLOW RATE OF CARRIER GAS AFFECTING THE KEY PARAMETERS OF GC-TCD FOR CO2, C3H8, AND CO ANALYSIS: AN EXPERIMENTAL INVESTIGATION - Zuas, Oman; Budiman, Harry (Teknologi Indonesia, 2016)
This paper reports on the effect of flow rate of helium (He) carrier gas on the key parameters of gas chromatography equipped with thermal conductivity detector (GC-TCD) for the measurement of carbon dioxide (CO2 ), propane (C3H8) and carbon monoxide (CO) in gravimetric standard gas mixture (Grav-SGM). The carrier gas has a function to transport vaporized molecules through the column during the GC separation process. The study provides opportunity to experimentally investigate the effect of gas flow rate on the several key parameters of the GC-TCD including retention time, peak area, peak height, response factor, resolution and selectivity. The results show that all key parameters were found to be carrier gas flow rate dependent. The increase of the gas flow rate could significantly decrease the retention time, peak area and response factor of the gas components. While both resolution and selectivity factor were observed to have a substantial decrease with increasing the flow rate of carrier gas. Therefore, proper selection of flow rate level of carrier gas is suggested before a GC measurement is carried out for obtaining an optimum condition.